Modeling Causal Relationships between Goal orientations and Beliefs of Academic Self-efficacy and Academic Achievement in the Sultanate of Oman - Alsaidi, Fahima; Aldhafri, Said (Dirasat: Educational Sciences, 2021)
This study aims to examine the mutual effects between students’ academic self-efficacy beliefs and their achievement goal orientations when both are examined concerning academic achievement. The sample consisted of 376 tenth-grade students from the Sultanate of Oman. The participants responded to two questionnaires examining academic self-efficacy beliefs and achievement goal orientations. To examine the best model that can explain the direct and indirect effects between the two predicting variables, the researchers utilized the AMOS25 software. The results indicated the existence of reciprocal effects between students’ academic self-efficacy beliefs and their achievement goal orientations in their relationship to academic achievement. Both proposed models obtained good fit indices and both explained relatively equal percentages of variance in academic achievement. That is, the model that had achievement goal orientation as a mediating variable explained 27% of the variance in academic achievement. A similar amount of variance (26%) was obtained by the model, where academic self-efficacy beliefs acted as a mediator.